RepD3D: A tool for representative period identification and associated boundary condition extraction - Clayton Cyril Soares; Arne Knies; Christian Winter (MethodsX, 2025)
Defining representative periods is a critical step for numerical modelers seeking to understand regional hydro- and morphodynamics in situations when long-term simulations are not feasible or future boundary conditions are unknown. However, identifying these periods and integrating the associated boundary conditions can be a time-intensive process. To address this, RepD3D has been developed as a Windows-based user interface, accompanied by open-source Python code, which helps users formulate and support modeling studies by employing a wind-based unfiltered reduction technique to identify representative periods. This tool is particularly beneficial for modelers investigating shallow-water wind-wave-driven processes or the influence of wind in their area of interest. For studies focusing on extreme events or specific wind directionality, RepD3D offers selective-class correlation, enabling users to identify representative periods for specific wind speed and direction classes. This approach avoids synthetic simulations and preserves the natural state within a simulation. Additionally, the application supports boundary condition extraction for user-defined models and conversion into Delft3D-4-compatible input files. RepD3D integrates water level and wave data from EasyGSH (1996–2016, German North Sea) and wind data from COSMO-REA6 (1995–2019, Europe), with its open-source design allowing for adaptation to other datasets. • RepD3D is a pre-compiled tool for Windows, designed to identify wind-based unfiltered and reduced representative periods and extract associated boundary conditions for modeling studies. • A modified version of the all-class correlation method, known as selective-class correlation, is introduced to identify representative periods specific to user-desired wind speeds and directions. • Boundary conditions for German North Sea (EasyGSH) and Europe (COSMO-REA6) are extracted and converted to DelftD3D-4-readable input files.